2002
DOI: 10.1007/s00299-002-0548-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved Agrobacterium -mediated transformation of sunflower ( Helianthus annuus L.): assessment of macerating enzymes and sonication

Abstract: Agrobacterium -mediated transformation of shoot apices of sunflower (Helianthus annuus L.) was evaluated following wounding by cell-wall-digesting enzymes and sonication. The frequency of explants with regenerated shoots expressing GUS (beta-glucuronidase) or GFP (green fluorescent protein) increased following treatment with the macerating enzymes cellulase Onozuka R-10 and pectinase Boerozym M5, whereas treatment with macerozyme R-10 had a negative effect. When a combination of cellulase (0.1%) and pectinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 17 publications
1
41
1
Order By: Relevance
“…Thus, the proper selection of a selective gene determines the possibility of success in the production of transgenic plants. Despite several publications in sunflower genetic transformation (Hewezi et al 2002;Weber et al 2003), there is no efficient or reproducible protocol with a low number of escapes, indicating that the selection method using Km is not effective. The aim of this work was to establish the use of the antibiotic Km as an efficient selective agent, trying to relate transgene presence with the differential in vitro behaviour.…”
mentioning
confidence: 99%
“…Thus, the proper selection of a selective gene determines the possibility of success in the production of transgenic plants. Despite several publications in sunflower genetic transformation (Hewezi et al 2002;Weber et al 2003), there is no efficient or reproducible protocol with a low number of escapes, indicating that the selection method using Km is not effective. The aim of this work was to establish the use of the antibiotic Km as an efficient selective agent, trying to relate transgene presence with the differential in vitro behaviour.…”
mentioning
confidence: 99%
“…With all of the tested varieties, we were able to obtain small plantlets of normal morphology, including shoots and roots ( Figure 2I-L). While Weber et al (2003) used grafting to obtain seeds from regenerated sunflower plants, no grafting was necessary for the sunflower varieties tested in our study. The regenerated plantlets of Hybrid Sunflower ( Figure 2M), Sonja ( Figure 2N), and Pacino ( Figure 2P) formed normal plants and developed flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to overcome these problems using wounded explants derived from immature seeds (Lucas et al 2000;Hewezi et al 2002Hewezi et al , 2003. Others have attempted to improve shoot regeneration systems from seedling shoot apical meristem explants by using sonication, macerating enzymes and/or wounding methods (Grayburn et al 1995;Scott and Vick 1995;Alibert et al 1999;Weber et al 2003). Weber et al (2000) reported successful shoot regeneration in some interspecific hybrid progenies.…”
mentioning
confidence: 99%
“…In Some countries, the highest percentage of the acreage of some economically important crops is transgenic; an increasing number of these transgenic varieties are or will soon be generated by Agrobacterium-mediated transformation (Gelvin, 2003 (Weber et al, 2003). Brassica is also a suitable host for Agrohacterium spp.…”
Section: Issn: 2320-5407mentioning
confidence: 99%